GC/MS Analyses of Thiosemicarbazones Synthesized from Acetophenones: Thermal Decay and Mass Spectra Features - Gastaca, Belén (2015)
The mass spectral fragmentation of thiosemicarbazones synthesized from acetophenones has been studied by CG/MS. These carbonyl compounds exhibit chromatographic peaks which are not observed in aliphatic analogues or those synthesized from aldehydes. The analysis of the corresponding spectra has allowed structural assignment to the dimerization of gas phase neutral fragments. Theoretical calculations (DFT level) also provide evidence to support the experimental observations.